New technique of total phalloplasty with re-innervated lattisimus dorsi myocutaneous free flap in female-to-male transsexuals - Ranno, Raul (2007)
The aim of this thesis is describing a new technique of total penile reconstruction in female-to-male transsexual, using re-innervated free latissimus dorsi myocutaneous flap to give to the patient ability for having sexual intercourse without the need for prosthesis.